Co-Protégé: Collaborative Ontology Building with Divergences - Díaz, Alicia (2006)
In this paper we present an innovative approach to develop a domain ontology in collaborative fashion. This approach is synthesized in a groupware application which is called Co-Protege, a set of plug-ins which extends Protege. This approach is innovative because Co-Protege enables the coexistence of divergent conceptualizations and the discussion thread in order to record the ontology evolution.